Continuum Mechanics using Mathematica® Fundamentals, Applications and Scientific Computing - Romano, Antonio. (Modeling and Simulation in Science, Engineering and Technology,, 2006)
This book's methodological approach familiarizes readers with the mathematical tools required to correctly define and solve problems in continuum mechanics. The book covers essential principles and fundamental applications, and provides a solid basis for a deeper study of more challenging and specialized problems related to elasticity, fluid mechanics, plasticity, materials with memory, piezoelectricity, ferroelectricity, magneto-fluid mechanics, and state changes. Key topics and features: * Concise presentation strikes a balance between fundamentals and applications * Requisite mathematical background carefully collected in two introductory chapters and two appendices * Recent developments highlighted through coverage of more significant applications to areas such as porous media, electromagnetic fields, and phase transitions Continuum Mechanics using Mathematica® is aimed at advanced undergraduates, graduate students, and researchers in applied mathematics, mathematical physics, and engineering. It may serve as a course textbook or self-study reference for anyone seeking a solid foundation in the field.